Comparative Radiologic Features of Pleural Thickening in Infective vs Non-Infective Etiologies - Ishtiaque Ali Langah, Ikram Ullah, Habibullah, Mahrukh Alizai, Irshad Ahmed, Jamshed Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Pleural thickening is a common radiologic finding, often indicating a variety of underlying pathologies. These pathologies can be classified into infective and non-infective causes, each with distinct radiologic features. Differentiating between these causes based on radiologic patterns can help guide clinical management. This study aims to compare the radiologic patterns of pleural thickening in infective versus non-infective causes. Methods: A retrospective analysis of 120 patients, diagnosed with pleural thickening and categorized into two groups based on etiology (infective vs non-infective), was performed. Radiologic features such as the pattern, location, and extent of pleural thickening were reviewed using chest X-rays and CT scans. Statistical analyses were used to compare the findings between the two groups. Results: Of the 120 patients, 60 had infective causes (e.g., tuberculosis, bacterial pneumonia) and 60 had non-infective causes (e.g., malignancy, asbestos-related disease). The infective group showed more heterogeneous pleural thickening, often associated with pleural effusions, while the non-infective group exhibited more localized, fibrotic pleural changes with occasional calcifications. Conclusions: The study highlights distinct radiologic patterns between infective and non-infective causes of pleural thickening. Identifying these patterns aids in differential diagnosis and treatment planning. Keywords: Pleural thickening, infective causes, non-infective causes, tuberculosis, malignancy, radiologic patterns.